2012
DOI: 10.1080/00207594.2012.662278
|View full text |Cite
|
Sign up to set email alerts
|

Met expectations and the wellbeing of diaspora immigrants: A longitudinal study

Abstract: Previous research has pointed to the importance of expectations for the adaptation of immigrants. However, most studies have been methodologically retrospective with only limited possibilities to show the optimal relationship between migrants' expectations and actual acculturation experiences for their wellbeing and other aspects of psychological adaptation. Moreover, previous research has been conducted mostly among sojourners and students. This longitudinal study focused on the relationship between premigrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 33 publications
3
44
0
3
Order By: Relevance
“…In general, the weaker than expected effects of acculturation attitudes could be due to the different association between attitudes and well-being in different acculturation domains, such as private and public (e.g., Navas et al, 2005). It thus could be possible that if assessed domain-specifically, attitudes related more to the private than to the public life sphere could have been more important predictors of well-being (e.g., Mähönen, Leinonen, & Jasinskaja-Lahti, 2013). Moreover, it might be the case that the way cultural maintenance is typically assessed (i.e., with reference to the cultural group of the country of origin) is not the most optimal for multiply identified individuals, such as the Ingrian Finnish respondents in our study.…”
Section: Covariates Of Life Satisfaction and Self-esteemmentioning
confidence: 97%
“…In general, the weaker than expected effects of acculturation attitudes could be due to the different association between attitudes and well-being in different acculturation domains, such as private and public (e.g., Navas et al, 2005). It thus could be possible that if assessed domain-specifically, attitudes related more to the private than to the public life sphere could have been more important predictors of well-being (e.g., Mähönen, Leinonen, & Jasinskaja-Lahti, 2013). Moreover, it might be the case that the way cultural maintenance is typically assessed (i.e., with reference to the cultural group of the country of origin) is not the most optimal for multiply identified individuals, such as the Ingrian Finnish respondents in our study.…”
Section: Covariates Of Life Satisfaction and Self-esteemmentioning
confidence: 97%
“…In addition, in one study by Tartakovsky and Schwartz, (2001;cited by Mahönen et al 2013) on young Jewish emigrants from Russia showed that security for oneself and one's family was a stronger motivation than motivators related to selfdevelopment, such as personal growth in knowledge and skills, and materialism, such as wealth and control over material resources, among people who chose Israel as their destination country, as compared to economically more developed countries such as Germany and the USA. A decision to emigrate to Finland, in the study by Mahönen, may have been driven by the expectations related to social relationships and the role of positive expectation confirmation, as discussed above, as opposed to the role of material welfare that is experienced as factor enhancing psychological wellbeing after migration (Mahönen et al 2013).…”
Section: Expectationsmentioning
confidence: 99%
“…Thus if the relevance of different kinds of expectations varies in different situations and contexts, it is possible that social relationships and free time is more important than one's economic situation and work life, such as in the context of diaspora migration from Russia to Finland as stated by Mahönen et al (2013), but job exhaustion can be related to TAWs job insecurity (Giunchi et al 2016). In addition, in one study by Tartakovsky and Schwartz, (2001;cited by Mahönen et al 2013) on young Jewish emigrants from Russia showed that security for oneself and one's family was a stronger motivation than motivators related to selfdevelopment, such as personal growth in knowledge and skills, and materialism, such as wealth and control over material resources, among people who chose Israel as their destination country, as compared to economically more developed countries such as Germany and the USA.…”
Section: Expectationsmentioning
confidence: 99%
“…Exploring emotions and well-being during the adaptation period provides a more multidimensional understanding of the integration of the migrant in the host country, including their sense of belonging there (Boccagni & Baldassar 2015). Previous research has identified the various factors that influence the adaptation period, including cultural aspects of the host country, language knowledge, religion, economic hardship, educational level, occupational trajectory, perceived discrimination, fulfilment of migration expectations, and social support (see, inter alia, Mähönen, Leinonen & Jasinskaja-Lahti 2013;Bak-Klimek et al 2015;Elgorriaga, Ibabe & Arnoso 2016). Adaptation and belonging might also depend on the difference between the two cultures and willingness of the individual to change (Bhugra 2004).…”
Section: Understanding the Linkages Between Migration And Psychosociamentioning
confidence: 99%